Acute Ischemic Stroke, Depressed Left Ventricular Ejection Fraction, and Sinus Rhythm: Prevalence and Practice Patterns. Issue 6 (27th January 2022) - Baker, Anna D.; Schwamm, Lee H.; Sanborn, Danita Y.; Furie, Karen; Stretz, Christoph; Mac Grory, Brian; Yaghi, Shadi; Kleindorfer, Dawn; Sucharew, Heidi; Mackey, Jason; Walsh, Kyle; Flaherty, Matt; et al.
Abstract : Background: There are limited data about the epidemiology and secondary stroke prevention strategies used for patients with depressed left ventricular ejection fraction (LVEF) and sinus rhythm following an acute ischemic stroke (AIS). We sought to describe the prevalence of LVEF ≤40% and sinus rhythm among patients with AIS and antithrombotic treatment practice in a multi-center cohort from 2002 to 2018. Methods: This was a multi-center, retrospective cohort study comprised of patients with AIS hospitalized in the Greater Cincinnati Northern Kentucky Stroke Study and 4 academic, hospital-based cohorts in the United States. A 1-stage meta-analysis of proportions was undertaken to calculate a pooled prevalence. Univariate analyses and an adjusted multivariable logistic regression model were performed to identify demographic, clinical, and echocardiographic characteristics associated with being prescribed an anticoagulant upon AIS hospitalization discharge. Results: Among 14 338 patients with AIS with documented LVEF during the stroke hospitalization, the weighted pooled prevalence of LVEF ≤40% and sinus rhythm was 5.0% (95% CI, 4.1–6.0%; I 2, 84.4%). Of 524 patients with no cardiac thrombus and no prior indication for anticoagulant who survived postdischarge, 200 (38%) were discharged on anticoagulant, 289 (55%) were discharged on antiplatelet therapy only, and 35 (7%) on neither. There was heterogeneity by site in the proportion discharged with an anticoagulant (22% to 45%, P <0.0001). Cohort site and National Institutes of Health Stroke Severity scale >8 (odds ratio, 2.0 [95% CI, 1.1–3.8]) were significant, independent predictors of being discharged with an anticoagulant in an adjusted analysis. Conclusions: Nearly 5% of patients with AIS have a depressed LVEF and are in sinus rhythm. There is significant variation in the clinical practice of antithrombotic therapy prescription by site and stroke severity. Given this clinical equipoise, further study is needed to define optimal antithrombotic treatment regimens for secondary stroke prevention in this patient population.